INTERRELATIONSHIPS OF CASHLESS ECONOMY, SERVICES OF TELECOMMUNICATION COMPANIES AND INDICATORS OF THE SHADOW ECONOMY: MODERN MODELING TECHNIQUES - Dotsenko, Tetiana; Shaparenko, Serhii; Humenna, Yuliia (Socio-economic relations in the digital society, 2023)
The article emphasizes that, under the influence of digitalization, trends in the organization of today’s world are changing, society’s opportunities are expanding, access to innovative things is increasing, and consumer demands are increasing. It is emphasized that in order to meet the needs of the population and business, the modern world of technological development is moving forward, expanding, allowing the introduction and widespread use of convenient, comfortable services of telecommunication companies, encouraging the development of cashless economy tools. The need to take into account the negative consequences of their widespread use, which include the possibility of illegal actions, fraud, and the development of a shadow economy, is noted. The main goal of the research is to determine modern methods of modeling the cashless economy, services of telecommunications companies, and the shadow economy, taking into account the interrelationships between these concepts. The article analyzes the literary achievements of international and domestic modern scientists regarding the focus of the interests of scientists studying the financial sphere on the research of the features of the cashless economy, the role of telecommunications companies, and the associated tinization of the economy. The relevance of determining modern methods of modeling the researched processes lies in the fact that digital technologies continue to improve, and the use of cashless economy tools, digital services of telecommunication companies will continue to grow, more and more consumers will implement digital transactions. And, accordingly, with the growth of the volume of non-cash transactions, the risk of possible abuses, frauds, and the growth of the shadowing of the economy increases. In the work, the research was carried out in four stages, which allow to determine different vectors in scientific research. A structural and logical diagram of relationships between the studied concepts is built. The latest effective methods of cashless economy modeling are highlighted. Modern effective methods of modeling services of telecommunications companies are highlighted. Modern methodical approaches to shadow economy modeling are described. The theoretical analysis of the literature, theoretical research methods (abstraction, synthesis, grouping) were used as methodological tools of the research; empirical research methods (description; observation), the resource base of the Scopus information platform; Figma design platform. The results obtained in the study will allow management personnel and the government to introduce clearer and stricter regulations on the security of digital, cashless services, strengthen the security policy of digital operations, improve the privacy of data and information, and create a safer environment for users of cashless, digital services.